2017
DOI: 10.1002/ejic.201601499
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structures, Optical Properties, and Phase Transitions of the Layered Guanidinium‐Based Hybrid Perovskites [C(NH2)3]2MI4; M = Sn, Pb

Abstract: The title compounds were obtained by the treatment of MI 2 in conc. HI with stoichiometric amounts of [C(NH 2 ) 3 ] 2 CO 3 . They show several phase transitions. The Pb/Sn HT phases {[C(NH 2 ) 3 ] 2 PbI 4 -I, Pnma, Z = 4, a = 13.04 Å, b = 13.62 Å, c = 9.36 Å} and {[C(NH 2 ) 3 ] 2 SnI 4 -I: a = 13.04 Å, b = 13.57 Å, c = 9.45 Å}, as well as [C(NH 2 ) 3 ] 2 PbI 4 -II (Pnnm, Z = 8, a = 27.03 Å, b = 9.31 Å, c = 12.92 Å) and [C(NH 2 ) 3 ] 2 SnI 4 -II (a = 26.89 Å, b = 9.30 Å, c = 12.94 Å) and also [C(NH 2 ) 3 ] 2 Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 40 publications
4
35
1
1
Order By: Relevance
“…The present study expands on the series of simple 2D guanidinium compounds that adopt the <110>-oriented RP perovskite type, originally obtained by Szafrański and coworkers [37][38][39] and recently revisited by the Hillebrecht's group. 40 The ACI perovskites reported in this work find join the very recently reported GACs n Pb n X 3n+1 compounds which adopt a similar crystal structure. 41 Here the ACI phase GAMA n Pb n I 3n+1 series (n = 1, 2 and 3) has been structurally characterized by means of single-crystal X-ray diffraction.…”
Section: Introductionsupporting
confidence: 85%
“…The present study expands on the series of simple 2D guanidinium compounds that adopt the <110>-oriented RP perovskite type, originally obtained by Szafrański and coworkers [37][38][39] and recently revisited by the Hillebrecht's group. 40 The ACI perovskites reported in this work find join the very recently reported GACs n Pb n X 3n+1 compounds which adopt a similar crystal structure. 41 Here the ACI phase GAMA n Pb n I 3n+1 series (n = 1, 2 and 3) has been structurally characterized by means of single-crystal X-ray diffraction.…”
Section: Introductionsupporting
confidence: 85%
“…Daub et al. found two phase transitions for 2 from measurements at different temperatures . The changes are mostly based on a progressively more symmetric arrangement of the inorganic part.…”
Section: Resultsmentioning
confidence: 98%
“…The structure of 2 is described in detail in the literature . Compound 2 forms a layered ⟨110⟩‐oriented perovskite structure (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deficit of Pb 2+ was also confirmed by EDX measurements. With MAPbI 3 and Gu 2 PbI 4 (Gu=guanidinium) as references, we found an I:Pb ratio of around 3.8:1 for crystals of the synthesis with x =0.25. Experiments have shown that crystals containing H 2 en are not stable in an electron beam but decompose with the release of iodine.…”
Section: Resultsmentioning
confidence: 75%